2015
DOI: 10.1007/s12517-015-1897-1
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous and Palaeocene clays of the northern Tunisia: potential use for manufacturing clay products

Abstract: Late Cretaceous and Palaeocene clay deposits of the northern Tunisia were studied for potential valorization in clay product manufacturing. To achieve this goal, physicochemical characterization based on multidisciplinary approaches including mineralogy, geochemistry and thermal analyses was carried out. Clay samples collected from the Bir M'Cherga and Tajerouine study sites have undergone chemical analysis by using atomic absorption spectroscopy. The obtained results showed that the studied samples were mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…corresponding to newly formed phases. Previous work showed that mullite and cristobalite substantially strengthened the mechanical resistance of the fired products (Felhi et al, 2008;Jeridi et al, 2008;Mahmoudi et al, 2008Mahmoudi et al, , 2010Hajjaji et al, 2009;Bennour et al, 2015;Ben M'barek-Jemaï et al, 2015).…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…corresponding to newly formed phases. Previous work showed that mullite and cristobalite substantially strengthened the mechanical resistance of the fired products (Felhi et al, 2008;Jeridi et al, 2008;Mahmoudi et al, 2008Mahmoudi et al, , 2010Hajjaji et al, 2009;Bennour et al, 2015;Ben M'barek-Jemaï et al, 2015).…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 98%
“…The desired industrial application depends on the physicochemical and mineralogical characteristics and thermal behaviour of the clays. Previous studies have focused on the suitability of Tunisian clays as raw materials for traditional ceramics (Baccour et al, 2008;Felhi et al, 2008;Jeridi et al, 2008;Mahmoudi et al, 2008Mahmoudi et al, , 2010Hajjaji et al, 2009;Ben M'barek-Jemaï et al, 2015;Bennour et al, 2015Bennour et al, , 2018Boussen et al, 2016;Ben M'barek-Jemaï et al, 2017). The thermal behaviour, the firing properties and ceramic applications of some Tunisian clays have also been investigated (Mahmoudi et al, 2010;Bennour et al, 2015).…”
mentioning
confidence: 99%
“…For the features of ceramics, clays made of pyrophyllite, talc, kaolinite, and montmorillonite are necessary [9]. Clay minerals are among the maximum ample minerals on Earth and are of substantial interest due to their low cost [10]. Natural clay deposits are the primary source of materials for light structural ceramics with good mechanical qualities including low shrinkage and heat transmission [11].…”
Section: Introductionmentioning
confidence: 99%
“…This area are located between 35˚15' to the south and 36˚8' to the north and meridians 8˚47' to the east and 8˚18' to the west (Figure 1), belongs to the topographic set of Upper Tell [7] marked by a limestone and marl-limestone geological substratum. Despite the number of studies launched in the extreme north Western Tunisia [8] [9], physicochemical and geotechnical characterization of Aptian limestones and their behavior remain unknown. The Aptian limestones…”
Section: Introductionmentioning
confidence: 99%